2013
DOI: 10.1016/j.bjane.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Evaluation of Nosocomial Infection Rates of the ICU

Abstract: The incidence of HAI in the ICU of our hospital was high, compared to the Turkish overall rates obtained at the Refik Saydam Center in 2007. When the rates of device-related infections between 2007 and 2008 were compared, they were higher in 2007. The rates of device- related infections were diminished in 2008 to below-national mean rates by infection control measures. Since the rate of urinary catheter-related infections are still high, we should exert continuous efforts for infection control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Antimicrobial resistance is a public health concern 1 . Among resistant pathogens, the bacterium Pseudomonas aeruginosa is of note because it is often associated with high rates of morbidity and mortality in patients in intensive care units (ICUs) 2 . P. aeruginosa is resistant to several antibiotics and has the ability to rapidly develop resistance to new antimicrobials.…”
mentioning
confidence: 99%
“…Antimicrobial resistance is a public health concern 1 . Among resistant pathogens, the bacterium Pseudomonas aeruginosa is of note because it is often associated with high rates of morbidity and mortality in patients in intensive care units (ICUs) 2 . P. aeruginosa is resistant to several antibiotics and has the ability to rapidly develop resistance to new antimicrobials.…”
mentioning
confidence: 99%
“…Hence, the impact of nosocomial infections is more significant in resource-poor countries. [16] Main problems in developing countries are understaffing, poor infrastructure in ICU and poor maintenance of records making situation difficult to get clarity on the incidence of these infections. Although it is difficult to solve some problems associated with financial hardship in developing countries, most solutions are simple and not resource demanding.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly many other studies reported by Dereli et al during a three-year period which were 53%, 29.15%, and 16.62% respectively. [11] A study in a hospital of North India observed an incidence rate of 33.5% in their respiratory ICU. [12] The infection rate observed in present teaching hospital indicates a relatively low prevalence of nosocomial infections, suggestive of good aseptic practices, hand hygiene principles and good ventilatory and urinary catheter care.…”
Section: Discussionmentioning
confidence: 99%